Conjunctival bacterial flora and antimicrobial susceptibility of captive and free‐living sea turtles in Brazil. (28th June 2018) - Cardoso‐Brito, Vinícius; Raposo, Ana Cláudia S.; Pires, Thaís T.; Pinna, Melissa H.; Oriá, Arianne P.
Abstract: Purpose: To describe the aerobic conjunctival bacterial flora of 3 especies of free‐living and under human care sea turtles and determine its antimicrobial susceptibility in vitro. Method: Thirty‐six sea turtles (72 eyes), juveniles and adults, 7 free‐living Chelonia mydas and 8 Chelonia mydas, 4 Caretta caretta, 11 Eretmochelys imbricata, and 6 Lepidochelys olivacea under human care, were evaluated. Conjunctival cultures were collected for identification of aerobic bacteria and antimicrobial susceptibility testing for ciprofloxacin, chloramphenicol, gentamicin, neomycin, oxacillin, polymyxin B, tetracycline, and tobramycin using antibiotic disks. Bacterial strains showing no sensitivity to 4 or more antimicrobials were considered multiresistant to this panel. Results: Bacterial growth was observed in 12/14 (85.71%) samples in the free‐living sea turtles, and there was growth in 100% (58/58) of the samples from captive animals. There were 94 strains isolated and 15 species identified. There was a predominance of Gram‐positive bacteria in free‐living Chelonia mydas, most of which were Bacillus and Staphylococcus . The most commonly isolated Gram‐negative species were enterobacteria for free‐living and under human care animals. The strains were predominantly sensitive to ciprofloxacin and tobramycin, and less sensitive to oxacillin or polymyxin B. Ten multiresistant strains were isolated. Yeast were identified in 13.89% (10/72) of the samples. Conclusions: These results, showing differences in the conjunctival bacterial flora of free‐living and captive animals, may be helpful for diagnosis and treatment of ocular disorders in sea turtles.